PENGARUH PEMBERIAN TERAPI RENDAM KAKI AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI STUDI PRE-EXPERIMENTAL - Yenni Anwar; Agnes Erlita Distriani Patade; Widyawati L. Situmorang (Universitas Widya Nusantara, 2026)
Hypertension that characterized by systolic blood pressure ≥140 mmHg and diastolic ≥90 mmHg, and it is often referred to as “the silent killer” because the symptoms are often not realized until complications occur. In hypertension treatment could be done by non- pharmacological therapies such as lifestyle modification, as well as complementary therapies such as hydrotherapy and physical exercise. One effective hydrotherapy method is warm water foot bath therapy, which the feet socked for 20 minutes in water at 39-40°C. The general purpose of this study was to analyze the impact of warm water foot bath therapy on reducng blood pressure toward hypertensive patients at Kawatuna Public Health Center. This is quantitative research with a One-group Pretest-Posttest Design approach. The total of population in this study were 186 hypertensive patients at Kawatuna PHC, and total of sample was 15 respondents that taken by using Purposive Sampling technique. The results of the study of 15 respondents showed that there is impact before and after administering of warm water foot soak therapy on reducing blood pressure toward hypertensive patients at Kawatuna Public Health Center with the Wilcoxon Test value p-value= 0.000 (p = ≤0.05). There is an Impact of Warm Water Foot Soaked Therapy on Reducing Blood Pressure Toward Hypertensive Patients at Kawatuna Public Health Center.